2014
DOI: 10.1002/ejoc.201403010
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Studies of a Triazole Analogue of Resorcylic Acid Lactone LL‐Z1640‐2

Abstract: A highly convergent and concise synthesis of a triazole analogue of resorcylic acid lactone natural product LL‐Z1640‐2 has been achieved from easily accessible starting materials in six linear steps in 18 % overall yield. Biological evaluation confirmed the enone system of the natural product is crucial for its activity. The triazole analogue showed good activity (IC50 7.2 μM) against MNK2 kinase, which is an emerging target for cancer chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…We envisaged that the exo-enone system can be converted from the corresponding macrocyclic exo-methylene allylic alcohol (6) which is to be formed by a Ni-catalysed, exoselective reductive coupling macrocyclisation of the alkynealdehyde (7) based on an intermolecular reaction reported by Takai et al 31 The cyclisation precursor ( 7) can be conveniently accessed by coupling three fragments (8, 9, 10) as previously reported. 29 This involves a Stille coupling of aryl triflate (8) with vinyl stannane (10) followed by transesterification on the protected resorcylate with (S)-pent-4-yn-ol (9) to introduce the top alkyne side chain. The vinyl stannane fragment (10), 29 which contains the requisite configurations of the two stereogenic hydroxy groups in 5, can be readily prepared from 2-deoxy D-ribose acetonide (11) via a Colvin rearrangement 32,33 followed by hydrostannylation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We envisaged that the exo-enone system can be converted from the corresponding macrocyclic exo-methylene allylic alcohol (6) which is to be formed by a Ni-catalysed, exoselective reductive coupling macrocyclisation of the alkynealdehyde (7) based on an intermolecular reaction reported by Takai et al 31 The cyclisation precursor ( 7) can be conveniently accessed by coupling three fragments (8, 9, 10) as previously reported. 29 This involves a Stille coupling of aryl triflate (8) with vinyl stannane (10) followed by transesterification on the protected resorcylate with (S)-pent-4-yn-ol (9) to introduce the top alkyne side chain. The vinyl stannane fragment (10), 29 which contains the requisite configurations of the two stereogenic hydroxy groups in 5, can be readily prepared from 2-deoxy D-ribose acetonide (11) via a Colvin rearrangement 32,33 followed by hydrostannylation.…”
Section: Resultsmentioning
confidence: 99%
“…29 This involves a Stille coupling of aryl triflate (8) with vinyl stannane (10) followed by transesterification on the protected resorcylate with (S)-pent-4-yn-ol (9) to introduce the top alkyne side chain. The vinyl stannane fragment (10), 29 which contains the requisite configurations of the two stereogenic hydroxy groups in 5, can be readily prepared from 2-deoxy D-ribose acetonide (11) via a Colvin rearrangement 32,33 followed by hydrostannylation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scheme 13 Synthesis of Sansalvamide-A analogue 126 In the same year, Goh et al reported the synthesis of a triazole analogue (157) of natural product LL-Z1640-2 and evaluated its biological activity (Scheme 16). 24 Initially, the commercially available 2,4,6-trihydroxybenzoic acid 146 was converted into the triflate 147 in three steps. The reaction progressed as the acetonide 148 underwent Colvin rearrangement in the presence of TMS diazomethane and n-BuLi to produce the alkyne 149 and further hydrostannylation produced the trans-vinyl stannane 150.…”
Section: Template For Synopen Thiemementioning
confidence: 99%
“…In 2014, synthesis and biological studies of a triazole analogue ( 90 ) of LL-Z1640-2 ( 3 ) were reported by the Chen group in 6 linear steps in 18% overall yield [ 50 ]. The triazole analog ( 90 ) showed good activity (IC 50 = 7.2 μM) against MNK2 kinase, which is an emerging target for cancer chemotherapy ( Scheme 18 ).…”
Section: Biological Activities and Chemistry Of Natural And Synthementioning
confidence: 99%